A tapestry of identity-based encryption: practical frameworks compared. (7th February 2008) - Boyen, Xavier
This paper surveys the practical benefits and drawbacks of several identity-based encryption schemes based on bilinear pairings. After providing some background on identity-based cryptography, we classify the known constructions into a handful of general approaches. We then describe efficient and fully secure IBE and IBKEM instantiations of each approach, with reducibility to practice as the main design parameter. Finally, we catalogue the strengths and weaknesses of each construction according to a few theoretical and many applied comparison criteria.